The impact of climate change on crop pests and diseases, and adaptation strategies for the Greater Mekong Sub-Region - Heong KL; Sivapragasam A; Loke WH; Chan FW; Khing SL; Sebastian, Leocadio S. (2015)
The workshop report provided evidences from numerous single factorial laboratory studies and modelling exercises that crop pests and diseases were affected by the vagaries of climate change viz., temperature, rainfall and wind patterns. There was also adequate support for the notion on the innate ability of crop pests and diseases to adapt to changing environmental conditions. It was revealed that organisms respond in different ways to various ecosystem templates thus lending credence to the fundamental need for one to be cognitive of organisms’ ecology and that of the nexus with ecosystem services. In contrast, it was recognized that there were conflicting messages on impacts of climate change on crop pests and diseases that were sent out to policy makers and farmers. Several key aspects were identified and the following needs for refinement were recognised: (i) Research designs that span across spatial and temporal landscapes; (ii) Effective modalities of communicating impacts to influence policies and changes and (iii) Re-designing policies and national agricultural frameworks to enhance resilience to climate changes (e.g. ecological engineering). The workshop highlighted several issues pertinent to climate impact on pests and diseases. The issues focused on the following questions: (i) The specific needs (viz. ecological and implementation) in the development of climate change adaptation strategies for P&D management, (ii) New policies or infrastructure that need to be designed to enhance sustainable agriculture, (iii) Policy change activities that could be initiated, and (iv) the key imperatives that need to be addressed to improve farmer livelihoods, learning and motivation. Overall, the workshop provided a valuable opportunity to take stock of the current state of affairs pertaining to the impact of climate change on crop pests and diseases and the adaptation strategies needed to plan and prepare the best set of collective actions in the face of climate change. The output list of recommendations and next steps will enable us to forge ahead with the directions and plans to diagnose and identify optimum efforts that will benefit the rural poor who are chronically vulnerable to the threats of climate change.